ANALISIS KONTEN DAKWAH VISUAL PADA AKUN INSTAGRAM @SAFARI_DAKWAH - Affan Fuhaid; Yono; Putri Ria Angelina (Jurnal Komunikasi, 2025)
Visual da'wah content must pay attention to various aspects in delivering its da'wah in terms of media and the material delivered must be appropriate and interesting so that it can be included as Islamic da'wah content. Visual da'wah through Instagram social media is utilized by the Instagram account @safari_dakwah in pouring out religious knowledge and creative ideas into visual designs with messages related to da'wah. This study formulates how the content of the da'wah message is contained in the content of the Instagram account @safari_dakwah. Then how @safari_dakwah packages visual da'wah content so that it can attract da'wah objects. This study uses a qualitative method using content analysis to determine the content of the da'wah message. Based on the data analysis carried out, it can be concluded that the Instagram account @safari_dakwah has filled the da'wah design such as messages of monotheism and morals with detailed content themes about personality, gratitude, Worship, Endeavor, and Thalibul 'ilmi. Then in packaging the design of the da'wah which is packaged using design elements such as points, lines, shapes, sizes, textures, contrasts, typography, colors, and principles such as rhythm, emphasis, balance, and unity that have been adjusted so that the design is easy to read, understand, attractive, and useful